A qualitative study of active travel amongst commuters and older adults living in market towns - Patricia E. Jessiman; Rosie E. Rowe; Russell Jago (BMC, 2023)
Abstract Background Being physically active is associated with better health, but rates of physical inactivity are high amongst adults in England. Active travel, defined as making routine journeys in physically active ways, has been identified as a potential solution. There is a lack of research into how modal shift towards active travel can be encouraged in market towns. The aims of the current study are to understand how new cycling and walking infrastructure and community activation projects might support modal shift to active travel amongst commuters and older adults in market towns. Methods This was a qualitative study using focus groups, 'go-along' interviews, and in-depth interviews as the main methods of data collection. Thirty-three participants (12 commuters and 21 older adults) took part across six focus groups. Eight of these also completed a go-along interview (4 walking, 4 cycling). Data were analysed using the Framework method of thematic analysis. Results Market towns have existing advantages for active travel, being relatively compact with most routine destinations within easy reach. The barriers to active travel faced by older adults and commuters in market towns are similar to those in cities; poor infrastructure remains the key barrier. Poorly maintained paths are hazardous for older pedestrians, and low-or-no lighting and lack of well-connected, delineated cycle routes deter both commuters and older adults. One factor which does appear qualitatively different to cities is participants' perception that the social norms of cycling differ in market towns. Conclusions Policies to promote active travel in market towns are most likely to be effective when they include measures targeted at both individual behaviour change and population level measures like large-scale infrastructure improvements. Initiatives to change the social norms around cycling may be required to increase active travel rates.